PENERAPAN METODE BERCERITA DAN BERNYANYI UNTUK MENINGKATKAN ASPEK PERKEMBANGAN ANAK DI PAUD MUTIARA ISLAMI PAGUTAN - Riah Riah; Nani Husnaini; Baiq Roni Indira Astriya (UIN Mataram, 2020)
The purpose of this study is to improve the developmental aspects of children in PAUD Mutiara IslamiPagutan through the application of storytelling and singing methods. The type of research used isClassroom Action Research with research subjects are 12 children aged 3-4 years. This research wasconducted in two cycles and each cycle consisted of three meetings. This research has an actionstage, namely planning, implementation, observation and reflection. Data analysis used is descriptiveanalysis. The results showed that the developmental aspects of the children an average valueobtained in the first cycle was 59.4% in the category of starting to develop (MB). Of the 12 children,11 were in the MB category, 1 child was in the Developing Base on Expectation (BSH) category. Basedon the result of children's learning completeness, 1 of 12 children was complete while the rest, 11children, was incomplete. Based on this result, the research is continued to cycle II. In cycle II theaverage number of children development observations was 77% in the category of Very GoodDevelopment (BSB), meaning that children have achieved individual accomplishment value. Three Ofthe 12 children indicated to be in the Developing Base on Expectation (BSH) category, 8 children arein the BSB category, and 1 child is in the MB category. Classical accomplishment of 11 children is inthe category of complete and 1 child is incomplete. Based on the result in cycle II, the study will notbe extended to next cycle, remaining at cycle II